STUDENTS' HIGHER ORDER THINKING SKILLS AND SELF REGULATED LEARNING ON GENERAL BIOLOGY COURSE OF FIRST SCIENCE STUDENTS' OF FMIPA UNIVERSITAS NEGERI MEDAN - Lisa Nurjannah; Hasruddin Hasruddin (Jurnal Pelita Pendidikan, 2023)
ABSTRACTThe aims of the study are to determine the application of higher order thinking skills and student self-regulated learning in the General Biology Course, Faculty of Mathematics and Natural Sciences, Universitas Negeri Medan. This research was conducted in the departments of Mathematics, Physics, Biology, Chemistry, Science and Computer Science. Sampling was done by random sampling, by taking 6 classes from different majors. The type of this research is descriptive-quantitative research. The number of higher order thinking skills tests was 15 items and self-regulated learning tests were 40 items. The test is validated first before being used as a research instrument, followed by a validity test of the instrument, a reliability test, a test of the level of difficulty and distinguishing power. The results showed that the application of students' higher-order thinking skills in the General Biology course at the Faculty of Mathematics and Natural Sciences was still in the low category. This can be seen from the results of the Mathematics Education class B, as much as 3% is in the perfect category, 28% is in the very good category, 7% is in the good category, and 60% is in the low category. In Physics Education class A, 38% are in the Perfect category, 38% are in the very good category, and 23% are in the low category. In the Biology A education class, 30% are in the perfect category, 5% are in the good category, and 65% are in the low category. In the Non-educational Chemistry class A, 28% were in the Perfect category, 17% were in the very good category, and 50% were in the low category. In IPA B class, 14% are in the perfect category, 28% are in the very good category, and 57% are in the low category. In computer science class C, 17% are in the perfect category, 33% are in the good category, and 50% are in the low category. Meanwhile, Self-Regulated Learning for Students of the Faculty of Mathematics and Natural Sciences in the General Biology course is included in good categories, this is because the application of the KKNI curriculum accustoms students to be able to study independently through the assignment of six compulsory assignments for students. Keyword: higher order thinking skills, self regulated learning, general biology.